Vakansi Yang Janggal Dan Penyakit Lainnya : Semantic And Semiotic Analysis Of The Variety Of Meanings From Film - Nanda Maulana; Erik Muhammad Pauhrizi (Universitas Pendidikan Indonesia, 2022)
Semiotics which is a branch of science from semantics which discusses the variety of meanings in language is also closely related to the concept of meaning in a sign or symbol, and in its development, semantics and semiotics are often used in the concept of telling meaning in films, either explicitly or explicitly, in this journal. will analyze the meaning in the film Vacancies That Awkward and Other Diseases directed by Yosep Anggi Noen, through the semantic and semiotic meanings that are implicitly or implicitly used in the film Vacations Yang Odd and Other Diseases, with qualitative research methods, which are the result of observing the works and data observation.